Lone star literacy: phenomenological insights into elementary writing instruction under new Texas literacy initiatives - Gray-Essex, Octavia (My University, 2025)
Third grade is a critical transitional year when students are expected to shift from “learning to read” to “reading to learn” (Fiester, 2010). Children move from developing foundational reading skills to proficiently using those skills for knowledge acquisition and comprehension across the curriculum. For decades, there has been a national campaign on the importance of third-grade reading proficiency and its impact on content mastery, graduation rates, and life beyond K–12 (Fiester, 2010). The urgency related to third-grade literacy instruction focuses primarily on reading, although writing is also a critical component of foundational literacy skills (Totten, 2004). This qualitative phenomenological study seeks to extend the body of foundational literacy research by examining the perceptions and experiences of third-grade educators teaching English Language Arts and Reading (ELAR) under the new literacy initiatives in Texas. In this investigation, the perspectives and experiences of educators will be examined to understand the factors that influence their instructional decision-making processes and teaching practices. Phenomenological methodology and sensemaking theory will be applied to data gathered through a focus group and follow-up interviews. By exploring teachers’ perceptions and experiences related to writing instruction, these findings support researchers, teachers, and other stakeholders' consideration of evidence-based writing instruction to determine how to best guide practitioners’ instructional practices and overcome the obstacles that impede student growth and achievement.
Keywords: Science of reading; Science of writing; Literacy initiatives; Texas; Third-grade; Writing instruction